Peran Kursus Nikah Membangun Keluarga Sejahtera - Khoiruddin Nasution (AHKAM : Jurnal Ilmu Syariah, 2015)
The birth of a number of family-related legislation and a number of technical rules related to the implementation of the Pre-Marriage Course, even used as one of the requirements to be able tocarry out the marriage, indicating that the program isconsidered so important. But in reality, the Pre-Marriage Courseis not going well, still aformalist.Therefore, these programs should receive serious attention and increasingly and developed according to the needs and the times. Therefore, the government should give serious attention to this issue before it becomes a problem that may threaten the quality generation.DOI: 10.15408/ajis.v15i2.2862